Effect of Vitamin E Supplementation on Copper and Zinc Levels in Plasma and Arsenic Level in Hair and Hoof of Arsenic Exposed Goats - Das, T. K.; Mani, V.; Kewalramani, N.; Kaur, H. (Indian Journal of Animal Nutrition, 2018)
The aim of the present experiment was to investigate effect of vitamin E supplementation on level of Cu and Zn in plasma and that of arsenic in hair and hoof in arsenic exposed goats. Twenty four crossbred lactating goats were randomly distributed into 4 groups of 6 animals each. All the animals including control group were fed basal ration to meet the requirement. The animals in groups T1, T2 and T3 were given arsenic @50 mg/kg DM while those in groupsT2 and T3 were additionally supplemented with vitamin E @100 IU and 150 IU/kg DM, respectively. The experiment lasted for 12 months. In all the groups, Zn decreased at the end of experiment while plasma Cu level was not affected. Plasma vitamin E level also decreased (P